Training Students to Analyze the Features of English-Kazakh Translation through Artificial Intelligence (Journal of Educational Sciences, 2026)
This scientific research explores training of future translators to critically analyze English-Kazakh translations through artificial intelligence.  The aim of the study is to develop and theoretically substantiate a methodical research for teaching students to analyze English-Kazakh translations through AI tools. The main objectives of the study are to correctly evaluate stylistic devices of AI translation presented in Kazakh language in order to increase the interest of students, to critically analyze the artificial intelligence product, to identify translation errors, to explain and prove ways to eliminate them, to provide a high-quality translation, to evaluate AI content, to teach students not to trust AI translation 100%, to check the accuracy of AI translation, to check the correctness of AI translation, to check the correctness of stylistic devices. In addition, in the learning process, students critically differentiate artificial intelligence products, form translation competence and develop the ability to interpret prose texts. The most effective ways proposed to eliminate several contradictions that were found during the analysis.  The methodical research is based on the analysis of scientific literature, comparative analysis of the original and translations proposed by AI, methods of conducting surveys and observation. Since the experiment was conducted through a mixed method, its participants selected as a simple random sample. The pedagogical experimental study involved 50 third-year students of Kazakh Ablai Khan University of International Relations and World Languages. The pedagogical experimental study consisted of three stages. In the experiment, it was found that the translation competence of the participants could be formed by critically analyzing artificial intelligence products. The conducted analysis showed that critical analysis of AI translations contributes to the formation of translation competence of students. The value of the study is determined by its contribution to the development of the methodical research for teaching literary translation in the context of digital transformation and unlimiting the scopes of using artificial intelligence in the educational process. The obtained practical significance of the results can be used when developing training programs, practical classes and the assessment materials for the training of future English-Kazakh professional translators.Keywords: artificial intelligence, future translator, critical analysis, AI products, translation competence.